BLENDED LEARNING BASIC REMOTE MODEL DI MASA PANDEMI COVID-19 PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VI MIN 3 BULELENG - Neny Rahmawati Neny Rahmawati (Balai Diklat Keagamaan Denpasar, 2021)
This study aims to find out the activities and learning outcomes of students of grade VI Madrasah Ibtidaiyah Negeri (MIN) 3 Buleleng in The Indonesian Language Subjects 2020/2021. In this study, 19 grade VI students were selected as research subjects. Data collection using test methods and observation methods. Data analysis in this study uses descriptive analysis that interprets qualitative and quantitative data. The results showed that: (1) There was an increase in the average percentage of student learning activities by 14%, from 63 in the less active category of cycle I to 77 or in the active category in cycle II, (2) There was an 8% increase in the average percentage of teacher activity, from 84 in either category.in cycle I to 92 or in the excellent category in cycle II, (3) There was an increase in the average percentage of student learning outcomes by 21% from 63 in cycle I to 84 in cycle II.